Memory Studies in the Nordic Countries: A Handbook - Guðmundsdóttir, Gunnþórunn,; Savolainen, Ulla, (Brill's Handbook Series in Memory Studies ;, 2025)
This peer-reviewed international handbook focuses on memory studies in the Nordic countries. It is a multi-disciplinary and transnational work that explores and maps characteristics and applications of the fast-growing field of memory studies in the Nordic region and in relation to the global context. With contributions focusing on theoretical and disciplinary reflections, illustrative thematic overviews, as well as elaborations of concepts and approaches in the Nordic setting, the handbook serves as a multi-disciplinary reference guide for researchers and students interested in memory studies. Existing and emerging debates have been carefully mapped, as well as disciplinary trajectories of the field, thematic, pragmatic, aesthetic, and ideological features of Nordic memory cultures. This comprehensive handbook of memory studies in the Nordic countries provides a stepping stone for future developments in the field.